INTEGRATING MAKNA AS FOUNDATION FOR CURRICULUM EDUCATION OF ACCOUNTING PROFESSIONS - Sewade, Jurana Nurdin (Accounting Department,, 2017)
This paper aims to uncover Â the role of moral values, akhlak[1], and nationalism (abbreviated as MAKNA[2]) in the curriculum of professional education accountant (PPAk). This is done to find out how important the moral values, akhlak values, and nationalime role and diitegrasikan in curriculum PPAk for accountants and candidates of Accountants. The approach used in this research is constructive approach. Informants in this study consists of 4 informants who can represent the accountants from various circles. The four informants are each representing IAI, PPAk Officers at a university in Indonesia, accountant educators PPAk and PPAk students who are still active lectures on PPAk. The idea of this paper arises because the dominant PPAk reality developed in Indonesia today represents the western education model, where the reality of accounting education is loaded with capitalistic, anthropocentric, pragmatic, and hedonic values. The findings of this study consist ofÂ 3, namely: first that moral values, akhlak, and nationalism in the curriculum PPAk is not necessary because the previous education has been given, in other words MAKNA in PPAk has been expired or expired because it has been given at ladder Education before. Secondly, that moral-related education, akhlak, and nationalism should be delegated to the relevant institutions dealing with education in that field certifed. Thirdly, moral values, akhlak, and nationalism in the curriculum of PPAk should be applied in order to increase moral awareness, akhlak, and nationalism for accountants in the future by integrating them in the existing curriculum, in the hope of creating accountants with high moral and akhlak, and Soulless nationalism. Curriculum Based on accounting education in accounting education is a necessity to be done in Indonesia in order to realize the liberation of accounting education from the domination of western capitalism.[1] AkhlakÂ in terminology means the behavior of a person who is needed by a conscious desire to do something good deeds. How to distinguish akhlak, morals, and ethics in the sense to determine good or bad human beings use benchmarks of reason, thought or ratio, in moral use benchmark norms that develop in society (customs). While in akhlak to determine both the bad use of Al-Quran and Al-hadith.[2] Makna in Indonesian is also called mean in English, which means to have meaning.